The Outcomes of Primary 23-gauge Vitrectomy in Retinal Detachment Patients with Grade C Proliferative Vitreoretinopathy Surgery - Hatice Nur Tarakçıoğlu; Burcu Kemer Atik; Abdullah Özkaya (Boğaziçi Tıp Dergisi, 2019)
INTRODUCTION[|]To assess the outcomes of primary vitrectomy in retinal detachment (RD) patients with grade C proliferative vitreoretinopathy (PVR).[¤]METHODS[|]In this study, retrospective, single-surgeon case series were examined. The patients who had an RD with grade C PVR and underwent 23-gauge vitrectomy, and had a minimum follow up period of 12 months were included. The primary outcome measure of this study was the anatomical success (achievement of the totally attached retina) rate after a single surgery.[¤]RESULTS[|]A total number of 42 eyes of 42 patients were included in this study. The mean age was 57.6+-13.9 years (range 27-88 years), and the mean follow-up was 17.1+-4.8 months (range 12-22 months). The anatomical success rate after a single operation was achieved in 32 of the 42 patients (76.2%). The remaining 10 patients were operated again, and the final success rate increased to 95.2% (40 of the 42 patients).[¤]DISCUSSION AND CONCLUSION[|]The findings suggest that vitrectomy is effective in the treatment of RD with grade C PVR with satisfactory anatomical success.[¤]